2016
DOI: 10.1097/md.0000000000003016
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Challenge of Multidrug-Resistant Gram-Negative Bacilli

Abstract: Colonization and infection by multidrug-resistant gram-negative bacilli (MDR GNB) in neonatal intensive care units (NICUs) are increasingly reported.We conducted a 5-year prospective cohort surveillance study in a tertiary NICU of the hospital “Paolo Giaccone,” Palermo, Italy. Our objectives were to describe incidence and trends of MDR GNB colonization and the characteristics of the most prevalent organisms and to identify the risk factors for colonization. Demographic, clinical, and microbiological data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 44 publications
4
17
1
Order By: Relevance
“… 1 2 3 The clinical and epidemiological impact of such antimicrobial resistance (AMR) is a worrisome trend posing severe limitations and challenges to clinicians and health care policymakers alike. 4 5 6…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 3 The clinical and epidemiological impact of such antimicrobial resistance (AMR) is a worrisome trend posing severe limitations and challenges to clinicians and health care policymakers alike. 4 5 6…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of colonization by multidrug resistant Gram-negative bacteria, such as E. coli and Klebsiella sp. in neonatal intensive care units (NICU) are correlated with length of NICU stay, and—indeed—exposure to ampicillin/sulbactam (Giuffrè et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study of infants admitted to a hospital in rural Kenya found that current breastfeeding was not protective against gut colonization with ESBL-producing E. coli at the time of admission nor during hospitalization [94]. A 5-year study of infants hospitalized in a neonatal intensive care unit in Italy also found that breastfeeding was not protective against ESBL-producing E. coli acquisition [95]. However, breastfed infants were less likely to become colonized with multidrug-resistant gram-negative bacteria during their stay.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%